Research methods in Psycholoy: evaluating a world of information - "Morling, Beth" (New York, 2012)
Research Methods in Psychology provides a comprehensive and readable introduction to methods for undergraduates. Employing a multi-method approach and exposing students to real examples of published research throughout the text, the authors provide students with the tools necessary to do good and ethical research in psychology and to understand the research they learn about in psychology courses and in the media. A wealth of pedagogical aids serve to break down the aversion and phobia that many students bring to a methods course
Keywords: Psychology-Research methodology